The Influence of Online Customer Review and Online Customer Ratings on Purchase Decisions in Tiktok Shop - Diva Klandy Lumansik; Yanda Bara Kusuma (Universitas KH. Abdul Chalim Mojokerto, 2025)
The increasing number of internet users in Indonesia has led to a shift in consumer shopping behavior towards online shopping. TikTok has developed the TikTok Shop feature, an online shopping platform that combines the social media experience with e-commerce. However, in online shopping, consumers cannot see products directly and lack information about the product and seller, leading to doubts and impacting purchase decisions. Customers may utilize online customer reviews and ratings to get information that they can use while making a purchasing decision. The purpose of this study is to examine how online customer reviews and ratings affect TikTok Shop purchases. This is a quantitative study with an associative approach. The population in this research is TikTok Shop users in Surabaya. The required sample size is 100 respondents. Purposive sampling is the method of sampling that is employed. Google Forms surveys were distributed to gather data. Multiple linear regression analysis was used to examine the data and determine how the variables related to one another. According to the findings of the t-test, online customer reviews and ratings significantly and favorably influence TikTok Shop customers' decisions to buy. The findings of the F test demonstrated that online customer reviews and ratings significantly and favorably influence TikTok Shop customers' decisions to buy.